2017
DOI: 10.1016/j.jos.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Centralization of extruded medial meniscus delays cartilage degeneration in rats

Abstract: We developed medial meniscus extrusion in a rat model, and centralization of the extruded medial meniscus by the pull-out suture technique improved the medial meniscus extrusion and delayed cartilage degeneration, though the effect was limited. Centralization is a promising treatment to prevent the progression of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…12 Furthermore, a preclinical study in rats reported that the use of this technique to treat medial meniscal extrusion due to transection of the meniscotibial ligament demonstrated significantly reduced extrusion and delayed the progression of osteoarthritis when compared with a control group. 20…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, a preclinical study in rats reported that the use of this technique to treat medial meniscal extrusion due to transection of the meniscotibial ligament demonstrated significantly reduced extrusion and delayed the progression of osteoarthritis when compared with a control group. 20…”
Section: Discussionmentioning
confidence: 99%
“…Meniscal extrusion initiates osteoarthritis (OA) and accompanies its progression [9][10][11]. Restoring the lost function caused by meniscus extrusion can delay OA progression [12].…”
Section: Introductionmentioning
confidence: 99%
“…36 Recent studies demonstrated promising results using surgical techniques such as arthroscopic pullout suture for meniscal root tears [37][38][39] or arthroscopic direct extrusion reduction to treat meniscal extrusion. 40,41 Studies comparing different approaches to treat posterior medial meniscal root tears found that anatomic transtibial pull-out root repair (with and without centralization suture into the posterior medial tibial plateau) best restored contact mechanics in the knee, compared with nonanatomic repair states, 42 while partial meniscectomy surgery or nonoperative management was associated with poor clinical outcomes and high arthroplasty rates. 43,44 Previous studies demonstrated that meniscal damage could be an important morphological risk factor for AKOA development: Roemer et al 13 identified meniscal extrusion and presence of meniscal abnormalities as risk factors for slow and fast tibiofemoral cartilage loss over 30 months comparing both types of cartilage loss to a reference group of knees without cartilage loss.…”
Section: Discussionmentioning
confidence: 99%